2019
DOI: 10.30595/jssh.v2i2.3431
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Environmental Awarness:The Role of Ethic Education

Abstract: Environmental damage that occurred in Indonesia in the last three decades is due to human behavior by exploiting and depleting the universe in order to meet the interests and needs of human's life. The objectives of this research were (1) to find out the direct effect of the students'environmental knowledge towards the environmental awareness, (2) to find out the indirect effect of the students' environmental knowledge towards the environmental awareness through ethics, (3) to find out the direct effect of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…EA is shown based on awareness, protection, and preservation, especially unfulfilled local potential. 4,5,21 This study contributes to a critical analysis of EA profiles through LISREL Second-order CFA by revealing latent variables or indicators (Figure 1 and Tables 2-3) that affect other indicators. The factor analysis indicates that the students' environmental care attitude is not only limited to caring, appreciating, and having good environmental ethics, but also includes making a real contribution and finding solutions to environmental problems that are integrated into the learning process.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…EA is shown based on awareness, protection, and preservation, especially unfulfilled local potential. 4,5,21 This study contributes to a critical analysis of EA profiles through LISREL Second-order CFA by revealing latent variables or indicators (Figure 1 and Tables 2-3) that affect other indicators. The factor analysis indicates that the students' environmental care attitude is not only limited to caring, appreciating, and having good environmental ethics, but also includes making a real contribution and finding solutions to environmental problems that are integrated into the learning process.…”
Section: Discussionmentioning
confidence: 92%
“…Simultaneously, our study holistically analyses the profile of students' EA by considering policies, plans, and environmentally sustainable programs. Furthermore, according to Murniawaty 5 and Widodo, 60 knowledge and commitment are needed to realise environmental protection and awareness, but they have not revealed how practical solutions can be used to implement them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That research identified a low implementation of environment-based learning, resulting in a lack of environmental character for students. 5,6 Environmental care, as it has been taught in school, refers to definitions, terms, concepts, and knowledge about the natural environment. The absence of the implementation of contextual learning can limit meaningful experiences for students.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of a preliminary survey of 15 teachers and 256 high school students in Wonosobo District, Central Java, Indonesia in March 2020, 5 it is observed that schools have shown 75% progress in policies towards environmental awareness, 62% progress in terms of promoting curriculum-based environmental studies, 56% participatory-based development of environmental activities, and 55% management of environmentally friendly school support facilities. That research identified a low implementation of environment-based learning, resulting in a lack of environmental character for students.…”
Section: Introductionmentioning
confidence: 99%